A mechanical comparison of the translational traction of female-specific and male soccer boots - Loud, D.; Grimshaw, P.; Kelso, R.; Robertson, W. S. P. (Science and Medicine in Football, 2026)
The studded outsole of a soccer boot provides additional traction to players to minimise the risk of slipping while performing high-speed manoeuvres. As excessive traction can lead to foot fixation and injury risk, there has been significant research surrounding the influence of stud configuration on the level of traction generated. This previous research, however, has predominately focused on the stud patterns, foot morphology and lower limb loading patterns of male players. As the popularity of women`s soccer increases, the aim of this investigation was to examine the differences in translational traction of female-specific soccer boots and male soccer boots currently available. A custom-built apparatus was used to determine the translational traction on both natural and artificial grass for four different movement directions. It was hypothesised that the female-specific boot in each pair would produce lower levels of translational traction as they are designed to be safer for female players who are more at risk of lower limb fixation injuries compared to males. An independent samples T-test showed that while there were some loading conditions where female boots produced lower translational traction compared to male boots, across all loading scenarios there was no significant difference between male and female boots (p = 0.818), thus the null hypothesis was rejected.